Czy czeska fantastyka po 1989 roku naprawdę jest o niczym? - Czaplińska, Joanna (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2014)
The aim of the paper is to present Czech science fiction literature after 1989 and its potential and perspectives in translationts to other languages. The author introduces the most interesting Czech novels that belong not to strictly commercial part of SF-F literature, but also contain „literary” values (as defined by Russian formalists): Utopie, nejlepší verze by Ivan Kmínek, Dlouhý den Valhaly by František Novotný, Peklo Beneš. O šťastnějším Československu by Josef Nesvadba, Engerlingové by Jaroslav Velinský, Spěšný vlak Ch. 24.12 by Jan Poláček, Stráűci noci by Sanča Fülle, a penthalogy Mycelium by Vilma Kadlečková. The author also tries to show that changes after 1989 on book market was for SF-F writers a „identity shock” and lead to „how to write” in the early 90’s. Contemporary Czech SF-F literature offers a wide range of topics and novels are addressed to a wide spectrum of readers who expect different experiences – from pure fun to ambitious problems. As author emphasizes, Czech SF-F is now a fully mature genre and many works of Czech writers are estimated at European and global level.
Keywords: Czech literature after 1989; Czech science fiction literature; Czech fantasy literature